ILMENITE AND TITANOMAGNETITE IN ROCKS OF THE TRAPROCK ASSOCIATION IN THE MALAYA BOTUOBUYA AND THE ALAKIT-MARKHA KIMBERLITE FIELDS, YAKUTIA - Podvysotskiy V.T.; Makarov A.S. (My University, 1987)
Titanomagnetite-ilmenite mineralization, i.e., the composition and the mode of occurrence of minerals and their relationships to each other and to gangue minerals, was studied by ore microscopy and by petrographic, X-ra microspectroscopic and X-ray diffraction analysis. Concentrations of ilmenite and titanomagnetite in traprock range from 1 to 6 vol. percent; the quantity of titanomagnetite in differentiated gabbro-dolerite and ferrogabbro of Permian-Triassic age increases to 15 vol. percent locally reaching 30 vol. percent in sideronitic patches. Several generations of ilmenite and titanomagnetite are recognizable by their mode of formation and relative time of crystallization. Besides primary ilmenite grains, which occur either independently or together with titanomagnetite, rocks of the traprock association contain secondary ilmenite as latticed exsolution textures in titanomagnetite grains.
Keywords: Permian; Triassic; Mesozoic::Triassic; Paleozoic::Permian; Мезозой::Триасовая; Палеозой::Пермская